Wallflowers - Joy, Mackenzie (Clarion Books, 2023)
"People call you a wallflower. Sometimes they call you shy. Sometimes they call you quiet, or maybe even scared. People think these are bad things, because sometimes they are LOUD. But you are happy just the way you are. And maybe you don't need to learn to be loud, they just need to learn to listen. Mackenzie Joy beautifully pairs her gorgeous illustrations with minimalist text in this heartwarming book that doesn't just acknowledge shy children, but celebrates them--because every wallflower deserves their chance to grow."